Preventing Gadget Addiction for Family Stability: A Critical Discourse Analysis of Prophetic Hadith in al-Kutub al-Sittah - Syanando Adzikri; Dimas Hutomo Putra; Marwan Mas'ud (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
Gadget addiction threatens family stability by disrupting communication, emotional bonds, and parental responsibilities in Muslim households. While research addresses psychological dimensions of digital addiction, the Islamic normative framework—particularly prophetic teachings—remains underexplored. This study examines how prophetic hadith provide ethical foundations for preventing gadget addiction and maintaining family stability. Using qualitative library research methodology, this study analyzes six hadith from al-Kutub al-Sittah addressing family leadership, accountability, kinship preservation, spiritual household vitality, gaze control, and wealth ethics. Data sources include Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan al-Tirmidhī, Sunan Abī Dāwūd, and classical commentaries, analyzed through Fairclough's Critical Discourse Analysis framework: textual, discourse practice, and sociocultural analysis. Findings reveal that prophetic hadith construct a holistic family defense system. The principle kullukum rā'in (leadership responsibility) establishes parental accountability for technology regulation as divine trust. The prohibition of qāṭi' raḥim (severing kinship) critiques emotional disconnection from gadget addiction. Teachings on household dhikr, gaze control, and wealth management provide spiritual, behavioral, and ethical frameworks for digital self-regulation. Gadget addiction is framed theologically as spiritual crisis manifesting in neglected leadership, wasted time and knowledge, and symbolic kinship severance. This study integrates Critical Discourse Analysis with thematic hadith studies (mawḍū'ī), demonstrating 7th-century prophetic teachings' relevance to 21st-century digital challenges. The research positions family stability as sakan wa ṭuma'nīnah (tranquility), achievable through prophetic guidance on technology ethics.